Tinjauan Yuridis Pengelolaan Kawasan Hutan dengan Tujuan Khusus dalam Kerangka Hukum Kehutanan: Kajian Literatur - M Farizh Fadhlulrahman; Andhara Naela; Rafi Nazori; M Rizky Putra; Zidan Akhbar Dharmawan; Rio Yuliansah; Ika Dwimaya Roza (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Special Purpose Forest Areas (KHDTK) are forest areas used for limited purposes, including research, education, training, and religious and cultural purposes, without altering the areas primary function. The regulation of Special Purpose Forest Areas (KHDTK) has evolved since its inception in Law Number 41 of 1999 concerning Forestry, and subsequent regulatory changes following the enactment of the legal basis for Special Purpose Forest Areas (KHDTK), the consistency of the hierarcy of laws and regulations, and legal issues in their implementation. The method used is normative legal research with a statutory approach and a conceptual approach through a literature review of previous laws and research. The results show that the regulation of Special Purpose Forest Areas (KHDTK) has evolved through six regulatory stages, with the main issue emerging after the issuance of Government Regulation Number 23 of 2021, which reinstated KHDTK despite tha lack of explicit delegation in the Job Creation Law, Furthermore, KHDTK management still faces various obstacles, such as encroachment, overlapping permits, tenure conflicts, and unclear boundaries. Therefore, its is necessary to strengthen the legal basis, accelerate the arrangement of regional boundaries, and involve the community in a participatory manner to increase the effectiveness of KHDTK management.